Le charisme de la raison - Breuer, Stefan (SocietàMutamentoPolitica, 2014)
When Max Weber introduced the concept of charisma into political sociology, he conceived of it not only as a quality of a person, but also as a symbolic form with a developmental history of its own, leading from magical to religious charisma, and finally to the charisma of reason. In this last form, Weber believed, charisma became, by way of routinization, one of the decisive factors for the formation of the modem rational state. But the charisma of reason developed only in France, during the Great Revolution of the 18th century, not in the United States. The essay discusses the reasons for this and shows that it is responsible for many differences in the political and administrative system of both countries.